Comorbid Feeding and Gastrointestinal Symptoms, Challenging Behavior, Sensory Issues, Adaptive Functioning and Quality of Life in Children and Adolescents with Autism Spectrum Disorder. (2nd January 2021) - Leader, Geraldine; O'Reilly, Mairéad; Gilroy, Shawn P.; Chen, June L.; Ferrari, Chiara; Mannion, Arlene
ABSTRACT: Aim: Children and adolescents diagnosed with an autism spectrum disorder (ASD) often demonstrate difficulties with feeding. The goal of the current study was to investigate co-occurring issues that often accompany feeding problems in 120 children and adolescents with ASD. Method : This study investigated the relationship between feeding problems and gastrointestinal symptoms, challenging behavior and sensory issues, quality of life, adaptive functioning and use of complementary and alternative medicine (CAM). Results : High rates of feeding problems, gastrointestinal symptoms, challenging behavior and sensory issues were endorsed by caregivers. Considerable differences were observed in the levels of gastrointestinal symptoms, challenging behavior, sensory issues, quality of life and CAM practices.Conclusion : The results of this study extend the present literature by highlighting comorbid conditions related to feeding problems and how feeding problems impact quality of life and adaptive behavior.